Method for fully utilizing rice husk biomass and product and application thereof
Through hydrothermal reaction and multi-step treatment of rice husk, multi-functional products for photoLED and zinc-ion batteries are prepared, which solves the problems of low rice husk utilization efficiency and environmental pollution in the existing technology, and realizes the use of rice husk. Comprehensive resource utilization and product performance improvement.
Patent Information
- Application Number
- CN202411392898.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art has problems such as single component utilization form and product, low efficiency and environmental pollution when dealing with rice husks, making it difficult to make full use of rice husk resources.
By reacting the water and heat in the solvent water in the solvent, the filter fluid and filter residue are separated, and the carbon material of the wood quality microsphere, carbon quantum dot solution and nickel sulfur sulfur is prepared through multiple steps. And zinc ion battery.
A comprehensive utilization of rice shells is realized, multi -functional products are prepared, the resource utilization rate is improved, environmental pollution is reduced, and the product has excellent luminous performance and electrochemical properties.
Smart Images

Figure HDA0005072923730000011 
Figure HDA0005072923730000012 
Figure HDA0005072923730000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomass materials and relates to a method for fully utilizing rice husk biomass and a product and application thereof. Background Art
[0002] Rice husk is one of the main by-products of the rice milling industry, accounting for about 20% of the mass of rice. my country's rice output is 180 million tons, and the by-product of rice husk is nearly 36 million tons. Effectively utilizing rice husk for deep processing of my country's agricultural and sideline products, turning agricultural biomass into treasure, and reducing environmental pollution have far-reaching significance.
[0003] At present, my country mainly processes rice husks into biomass fuel particles using equipment. This fuel can replace coal and be directly burned in boilers to generate electricity or heat. The burnt ash can also be used as organic fertilizer for agricultural production. However, there are a lot of crude fibers and silicon in rice husks, which leads to strong friction characteristics and easy grinding equipment, greatly increasing the processing cost. Therefore, the method for processing rice husks still has limitations, and the component utilization form and product are single, and the efficiency is low. The method for processing rice husks provided by the present invention can effectively overcome the above problems. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for fully utilizing rice husk biomass and preparing products with different functions in view of the defects of the above-mentioned prior art, which fully realizes the classification and all-round utilization of rice husks. The preparation process is safe, green and environmentally friendly. While obtaining lignin microspheres, a carbon quantum dot solution as a fluorescent film material for photo-LEDs and a new type of rice husk biocarbon material as a zinc ion battery can also be obtained, which have excellent luminescence performance and electrochemical performance respectively.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0006] A method for fully utilizing rice husk biomass and preparing products with different functions comprises the following steps:
[0007] (1) adding rice husks to solvent water, stirring for a certain period of time to perform a hydrothermal reaction, and then filtering to obtain a filtrate A and a filter residue B;
[0008] (2) adding o-phenylenediamine, phosphoric acid and sulfuric acid to the filtrate A obtained in step (1), stirring and mixing, and placing in a reactor for hydrothermal reaction. After the hydrothermal reaction is completed, filtering with a water-based microporous filter membrane, collecting the filtrate C and dialyzing it to obtain a carbon quantum dot solution (CDs solution);
[0009] (3) treating the filter residue B obtained in step (1) with a low eutectic solvent to obtain lignin microspheres and delignified filter residue D, respectively;
[0010] (4) Dispersing the filter residue D and nickel nitrate, iron nitrate, urea and ammonium fluoride in solvent water, stirring for a certain period of time and then performing preliminary hydrothermal treatment, filtering and collecting the solid, then adding thioacetamide (TAA) and ethanol, stirring for a certain period of time and then performing secondary hydrothermal treatment, filtering and collecting the filter residue E;
[0011] (5) The filter residue E is carbonized in a tube furnace, washed with hydrochloric acid and water after carbonization, and dried to obtain a nickel-iron-sulfur loaded carbon material (Ni-Fe-SNC carbon material).
[0012] According to the above scheme, in step (1), the concentration of rice husk added to the solvent water is 80-120 g / L, the stirring time is 15-60 min, the temperature of the hydrothermal reaction is 160-200° C., and the time is 0.3-1 h.
[0013] According to the above scheme, in step (2), the stirring time is 15-60 minutes; the temperature of the hydrothermal reaction is 160-200° C., and the time is 8-12 hours. Such hydrothermal reaction conditions effectively control the reaction temperature while ensuring the formation of a uniform nano-sized CDs solution, shorten the reaction time, and reduce the energy consumption of the process; the filtration is performed using a water-based microporous filtration membrane with a pore size of 0.4-0.5 μm; the dialysis uses a dialysis bag with a molecular weight of 1000-4000 MW, and the dialysis time is 60-80 hours; the mass of o-phenylenediamine is 5%-15% of the rice husk used to obtain the filtrate A, and the volume of phosphoric acid and sulfuric acid is 5%-15% of the filtrate A.
[0014] According to the above scheme, the CDs solution obtained in step (2) is a red fluorescent CDs solution with a size of 0.1-1 nm and good fluorescence characteristics and photostability. The CDs solution has a characteristic fluorescence peak within the wavelength range of 500-650 nm under the excitation of ultraviolet light with a wavelength of 550-750 nm.
[0015] According to the above scheme, in step (3), the low eutectic solvent consists of lactic acid and choline chloride, and the concentration of choline chloride added to the lactic acid is 110-130 g / L.
[0016] According to the above scheme, in step (3), the process of delignifying the filter residue B with a low eutectic solvent is as follows: adding the filter residue B to the low eutectic solvent (the concentration of the filter residue B in the low eutectic solvent is preferably 10-20 g / L), then heating it in an oil bath to 80-200° C. for 8-15 hours, then adding a large amount of ethanol (the volume of ethanol is generally 2-4 times the volume of the low eutectic solvent) and standing overnight, then filtering to obtain a filtrate F and a delignified filter residue D; evaporating the ethanol from the filtrate F, then adding a large amount of deionized water (the volume of deionized water is generally 2-4 times the volume of the filtrate F) and standing overnight, and finally centrifuging to obtain lignin.
[0017] According to the above scheme, the lignin obtained in step (3) can be further prepared into lignin microspheres (LMPs) using γ-valerolactone and glycerol, and the specific process is: adding lignin to a mixture of γ-valerolactone and glycerol, and then stirring at a temperature of 70-100°C for 20-60 minutes, then adding deionized water and stirring for 0.5-1h, and centrifuging to obtain LMPs. Among them, the addition concentration of lignin is 0.5-5g / L; in the mixture of γ-valerolactone and glycerol, the volume percentage of γ-valerolactone is 5%-15%, and the balance is glycerol; the volume amount of deionized water is 0.5-1.5 times that of the mixture of γ-valerolactone and glycerol.
[0018] According to the above scheme, in step (4), the concentrations of nickel nitrate, nickel nitrate, urea and ammonium fluoride added to the solvent water are all 5-15 g / L, and the concentration of filter residue D added to the solvent water is 25-75 g / L; after preliminary hydrothermal treatment, the concentration of the solid collected by filtration in the solvent ethanol is 80-120 g / L, and the concentration of thioacetamide in the solvent ethanol is 10-30 g / L; the temperature of the two hydrothermal treatments is 100-120° C., the time is 8-10 h, and the stirring time is 1-2 h.
[0019] According to the above scheme, in step (5), the carbonization temperature is 700-800°C, the carbonization time is 0.5-3h, and the temperature is raised to the carbonization temperature at a heating rate of 3-10°C / min. This carbonization condition ensures effective carbonization while being simple to operate, effectively controlling the reaction temperature, reducing power consumption, and reducing process energy consumption.
[0020] The CDs solution prepared by the above method can be used for the fluorescent film of photoinduced LED. The specific application method is: mix ethanol and CDs solution in a volume ratio of 1:1, and then mix the mixture of ethanol and CDs solution with silica gel in a volume ratio of 1:1 and apply it on the surface of the lampshade. After air drying, a fluorescent film can be formed on the surface of the lampshade, and the photoinduced LED can emit red light after power is turned on.
[0021] The nickel-iron-sulfur loaded carbon material prepared by the above method is used as the positive electrode of a zinc ion battery. The specific application method is: the carbon material is mixed with a conductive agent and a binder solvent (such as 1-methyl-2-pyrrolidone (NMP)) and then evenly coated on an aluminum foil as the positive electrode, a zinc sheet is used as the negative electrode, and a zinc sulfate solution is used as the electrolyte to assemble a zinc ion battery.
[0022] The present invention uses rice husk as a carbon source, and after grading the rice husk, lignin microspheres are obtained, and CDs solution and carbon materials can also be obtained, which are used as fluorescent film materials for light-induced LEDs and carbon materials for zinc ion batteries, respectively. Compared with the prior art, the above technical solution conceived by the present invention can achieve the following beneficial effects:
[0023] (1) The present invention solves the problems of limited raw material sources for preparing fluorescent CDs solution in the prior art, high pollution and high price of chemical reagents used in the preparation process. Moreover, the CDs solution prepared by the present invention has good fluorescence characteristics and photostability, good dispersibility, low toxicity and good biocompatibility. In the application of CDs solution, its fluorescence characteristics can be fully utilized to prepare it into a fluorescent film for photoinduced LED, which greatly saves costs and is environmentally friendly.
[0024] (2) The present invention extracts lignin through a low eutectic solvent and can further process it to obtain lignin microspheres (LMPs), which are non-toxic, harmless, and green.
[0025] (3) Compared with pure carbon-based materials, the nickel-iron-sulfur-loaded carbon material prepared by the present invention has excellent electrochemical properties and can be used in zinc-ion batteries. For example, the assembled zinc-ion battery provides excellent specific capacitance, power density and energy density at a current density of 1A / g. In addition, the nickel-iron-sulfur-loaded carbon material prepared by the present invention has little harm to the environment. Its application in zinc-ion batteries can alleviate the dilemma of battery recycling to a certain extent, is beneficial to environmental protection, and also provides new ideas for the future research and development of energy storage materials with high energy density and high power density.
[0026] As described above, the present invention makes use of rice husks to the greatest extent in terms of raw material utilization, and the filter residue and filtrate of the raw materials are fully utilized to make products with different functions, which not only solves the current limitations in the application of rice husks, but also maximizes the economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the particle size distribution diagram of the CDs solution prepared in Example 1.
[0028] Figure 2 1 is a fluorescence spectrum diagram of the CDs solution prepared in Example 1 at different excitation wavelengths.
[0029] Figure 3 This is the spectrum of the photo-LED prepared in Example 1.
[0030] Figure 4 is a scanning electron microscope image (SEM) of the LMPs prepared in Example 1.
[0031] Figure 5 This is a scanning electron microscope image (SEM) of the Ni-Fe-SNC carbon material prepared in Example 1.
[0032] Figure 6 This is a constant current charge and discharge test diagram of the assembled zinc ion battery of the Ni-Fe-SNC carbon material prepared in Example 1.
[0033] Figure 7 This is a power density-energy density diagram of the assembled zinc ion battery of the Ni-Fe-SNC carbon material prepared in Example 1. DETAILED DESCRIPTION
[0034] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the present invention is not limited to the following embodiments.
[0035] Example 1
[0036] A method for fully utilizing rice husk biomass, the specific steps are as follows:
[0037] (1) 10 g of rice husk was added to 100 mL of deionized water, stirred for 0.5 h, reacted in a hydrothermal reactor at 180 °C for 0.5 h, and then filtered to obtain about 100 mL of filtrate A and about 10 g of filter residue B.
[0038] (2) 1 g o-phenylenediamine, 10 mL phosphoric acid and 10 mL sulfuric acid were added to the filtrate A in sequence, and the mixture was stirred for 0.5 h and reacted in a hydrothermal reactor at 180° C. for 10 h. After the reaction, the mixture was filtered using a water-based microporous filtration membrane with a pore size of 0.45 μm to obtain a filtrate C. The filtrate C was dialyzed using a 3000 MW molecular weight dialysis bag for 72 h to obtain a CDs solution (the solution in the dialysis bag was a CDs solution, which had good dispersion and no obvious agglomeration when observed with the naked eye).
[0039] (3) The residue B obtained in step (1) is added to a low eutectic solvent (558.81 mL of lactic acid and 69.81 g of choline chloride are stirred at 80° C. for 1 h to obtain a uniform transparent liquid), the oil bath temperature is 100° C., the heating time is 12 h, and then a large amount of ethanol (the volume of ethanol is 3 times the volume of the low eutectic solvent) is added and allowed to stand overnight, followed by filtration to obtain a filtrate F and a delignified residue D; the ethanol is evaporated from the filtrate F, and then a large amount of deionized water (the volume of deionized water is 3 times the volume of the filtrate F) is added and allowed to stand overnight, and finally centrifuged to obtain lignin (about 1 g).
[0040] (4) 0.1 g of the lignin extracted in step (3) was dissolved in a mixed solution of 10 mL of γ-valerolactone and 90 mL of glycerol, followed by stirring at 80 °C for 0.5 h. Finally, 50 mL of deionized water was added and stirred for 0.5 h, followed by centrifugation to obtain LMPs.
[0041] (5) 1 g nickel nitrate, 1 g ferric nitrate, 1 g urea and 1 g ammonium fluoride and 5 g delignified residue D were added to 100 mL deionized water, and the mixture was stirred for 1 h and reacted at 100 °C in a hydrothermal reactor for 10 h. The solid (about 5 g) was collected by filtration. Subsequently, 1 g TAA and 50 mL ethanol were added, and the mixture was stirred for 2 h and reacted at 120 °C in a hydrothermal reactor for 8 h. Finally, the residue E was collected by filtration. The residue E was dried and carbonized in a tubular furnace at a carbonization temperature of 700 °C, a heating rate of 5 °C / min, and a time of 1 h. After the carbonization, the residue was rinsed with hydrochloric acid and water, and dried to obtain a nickel-iron-sulfur-loaded carbon material (Ni-Fe-SNC carbon material).
[0042] like Figure 1 As shown, the size of the CDs solution prepared in Example 1 is between 0.45-0.55 nm and the distribution is relatively uniform.
[0043] like Figure 2 As shown, the CDs solution prepared in Example 1 has significant fluorescence characteristics under the ultraviolet excitation wavelength of 580-620nm, and has a characteristic fluorescence peak near the wavelength of 648nm.
[0044] like Figure 4 As shown, through scanning electron microscopy observation, it was found that lignin was spherical after heat exchange with the mixture of γ-valerolactone and glycerol, indicating that lignin was successfully prepared into LMPs.
[0045] Application 1: The CDs solution prepared in Example 1 is used for the fluorescent film of light-induced LED. The specific application method is: ethanol and CDs solution are mixed at a volume ratio of 1:1, and then the mixture of ethanol and CDs solution is mixed with silica gel (commercially available LED-specific silica gel, which is made of A glue and B glue mixed at a mass ratio of 2:1) at a volume ratio of 1:1 and then applied to the surface of the lampshade (the lampshade area is about 56mm 2 ), after air drying, a fluorescent film will be formed on the surface of the lampshade, and after power is turned on, the light-induced LED can emit red light. The relevant data is measured with a handheld illuminance meter, and the spectrum is as follows Figure 3 As shown, red light accounts for 95.6%, which corresponds exactly to the red fluorescent carbon dots.
[0046] Application 2: The Ni-Fe-SNC carbon material prepared in Example 1 is used in zinc ion batteries. The specific process is as follows: the Ni-Fe-SNC carbon material is mixed with a conductive agent and a binder solvent (such as 1-methyl-2-pyrrolidone (NMP)) and then uniformly coated on an aluminum foil as a positive electrode, a zinc sheet as a negative electrode, and a 1M zinc sulfate solution as an electrolyte to assemble a zinc ion battery. After standing overnight, the electrochemical performance is tested using an electrochemical workstation.
[0047] like Figure 6 and Figure 7 As shown, the battery provides an ultra-high specific capacitance of 441F / g at a current density of 1A / g, and an energy density of up to 270Wh / kg when the power density is 1050W / kg.
[0048] Example 2
[0049] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction temperature in step (2) is 200° C., and the prepared CDs solution has a characteristic fluorescence peak in the green light wavelength range under the excitation of ultraviolet light with an excitation wavelength of 580-620 nm.
[0050] Example 3
[0051] The difference between this embodiment and the application 1 in the embodiment 1 is that the dichloromethane and the CDs solution are mixed evenly, and then the obtained mixture is mixed evenly with the silica gel and then coated on the surface of the lampshade (the lampshade area is about 56mm 2 ), after air drying, a fluorescent film will be formed on the surface of the lampshade, and after power is turned on, the photoinduced LED will emit light red light.
[0052] Example 4
[0053] The difference between this embodiment and embodiment 1 is that in step (5), the tube furnace is heated to 700°C at 10°C / min and kept warm for 1 hour. The Ni-Fe-SNC carbon material prepared in this embodiment is assembled into a zinc ion battery with reference to "Application 2". After standing overnight, its electrochemical performance is tested using an electrochemical workstation. The battery provides an ultra-high specific capacitance of 389F / g at a current density of 1A / g, and an energy density of up to 202Wh / kg when the power density is 1012W / kg.
[0054] Example 5
[0055] The difference between this embodiment and embodiment 1 is that in step (5), the tube furnace is heated to 700°C at 5°C / min and kept warm for 2h. The Ni-Fe-SNC carbon material prepared in this embodiment is assembled into a zinc ion battery with reference to "Application 2". After standing overnight, its electrochemical performance is tested using an electrochemical workstation. The battery provides an excellent specific capacitance of 421F / g at a current density of 1A / g, and an energy density of up to 255Wh / kg when the power density is 1045W / kg.
[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for fully utilizing rice husk biomass, characterized in that: The following steps are involved: (1) adding rice husks to solvent water, stirring evenly, performing a hydrothermal reaction, and then filtering to obtain a filtrate A and a filter residue B; (2) adding o-phenylenediamine, phosphoric acid and sulfuric acid to the filtrate A obtained in step (1), stirring evenly and then performing a hydrothermal reaction. After the hydrothermal reaction is completed, filtering with a water-based filter membrane, collecting the filtrate C and performing dialysis to obtain a carbon quantum dot solution; (3) treating the filter residue B obtained in step (1) with a low eutectic solvent to obtain lignin microspheres and delignified filter residue D, respectively; (4) Dispersing the filter residue D and nickel nitrate, iron nitrate, urea and ammonium fluoride in solvent water, stirring evenly and then performing preliminary hydrothermal treatment, filtering and collecting the solid, then adding thioacetamide and ethanol, stirring evenly and then performing secondary hydrothermal treatment, filtering and collecting the filter residue E; (5) The filter residue E is carbonized in a tubular furnace, washed after carbonization, and dried to obtain a nickel-iron-sulfur loaded carbon material.
2. The method for fully utilizing rice husk biomass according to claim 1, characterized in that: In step (1), the concentration of rice husk added to the solvent water is 80-120 g / L; the temperature of the hydrothermal reaction is 160-200° C., and the time is 0.3-1 h.
3. The method for fully utilizing rice husk biomass according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal reaction is 160-200° C., and the time is 8-12 hours; the mass of o-phenylenediamine is 5%-15% of the rice husk used to obtain filtrate A, and the volumes of phosphoric acid and sulfuric acid are both 5%-15% of the filtrate A.
4. The method for fully utilizing rice husk biomass according to claim 1, characterized in that: In step (2), filtration is performed using a water-based microporous filtration membrane with a pore size of 0.4-0.5 μm; dialysis uses a dialysis bag with a molecular weight of 1000-4000 MW, and the dialysis time is 60-80 hours; the carbon quantum dot solution is a red fluorescent carbon quantum dot solution, the carbon quantum dot size is 0.1-1 nm, and under the excitation of ultraviolet light with a wavelength of 550-750 nm, it has a characteristic fluorescence peak in the wavelength range of 500-650 nm.
5. The method for fully utilizing rice husk biomass according to claim 1, characterized in that: In step (3), the process of delignifying the filter residue B with a low eutectic solvent is as follows: adding the filter residue B to the low eutectic solvent, then heating it in an oil bath to 80-200° C. for 8-15 hours, then adding ethanol and standing overnight, then filtering to obtain a filtrate F and a delignified filter residue D; evaporating the ethanol from the filtrate F, then adding deionized water and standing overnight, and finally centrifuging to obtain lignin; wherein the low eutectic solvent is composed of lactic acid and choline chloride, and the concentration of choline chloride added to the lactic acid is 110-130 g / L.
6. The method for fully utilizing rice husk biomass according to claim 5, characterized in that: Lignin is further prepared into lignin microspheres using gamma-valerolactone and glycerol. The specific process is: lignin is added into a mixture of gamma-valerolactone and glycerol, and then stirred at a temperature of 70-100°C for 20-60 minutes, then deionized water is added and stirred for 0.5-1h, and lignin microspheres are obtained by centrifugation; wherein the addition concentration of lignin is 0.5-5g / L; in the mixture of gamma-valerolactone and glycerol, the volume percentage of gamma-valerolactone is 5%-15%, and the remainder is glycerol; and the volume amount of deionized water is 0.5-1.5 times that of the mixture of gamma-valerolactone and glycerol.
7. The method for fully utilizing rice husk biomass according to claim 1, characterized in that: In step (4), the concentrations of nickel nitrate, nickel nitrate, urea and ammonium fluoride added to the solvent water are all 5-15 g / L, and the concentration of filter residue D added to the solvent water is 25-75 g / L; after preliminary hydrothermal treatment, the concentration of the solid collected by filtration in the solvent ethanol is 80-120 g / L, and the concentration of thioacetamide in the solvent ethanol is 10-30 g / L; the temperature of the two hydrothermal treatments is 100-120° C., the time is 8-10 h, and the stirring time is 1-2 h.
8. The method for fully utilizing rice husk biomass according to claim 1, characterized in that: In step (5), the carbonization temperature is 700-800° C. and the carbonization time is 0.5-3 h. After the carbonization is completed, the material is washed with hydrochloric acid and water.
9. Application of the carbon quantum dot solution prepared by the full utilization method of claim 1 as a fluorescent film material for photo-induced LEDs, characterized in that: The specific application method is: mix ethanol and carbon quantum dot solution, and then mix them evenly with silica gel, apply them on the surface of the lampshade, and after air drying, a fluorescent film can be formed on the surface of the lampshade, and photoluminescence can be achieved after power is turned on.
10. Application of the nickel-iron-sulfur loaded carbon material prepared by the full utilization method of claim 1 as a positive electrode of a zinc ion battery, characterized in that: The specific application method is: the carbon material is mixed with a conductive agent and a binder with a solvent and then evenly coated on an aluminum foil as a positive electrode, a zinc sheet is used as a negative electrode, and a zinc sulfate solution is used as an electrolyte to assemble a zinc ion battery.